2017
DOI: 10.1016/j.matchar.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

X-ray micro computed tomography characterization of cellular SiC foams for their applications in chemical engineering

Abstract: Open-cell SiC foams clearly are promising materials for continuous-flow chemical applications such as heterogeneous catalysis and distillation. X-ray micro computed tomography characterization of cellular β-SiC foams at a spatial voxel size of 13.6 3 μm 3 and the interpretation of morphological properties of SiC open-cell foams with implications to their transport properties are presented. In-situ draining experiments were carried out in order to understand the nature of the residual static liquid hold-up in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…The BJH pore size distribution of the TPAOH treated samples shows random mesopores and macropores in the range 10 nm to 160 nm (Figure 2b and Figure S1c), and the pore size increase with the concentration of TPAOH. In liquid phase reactions, the diffusivity of species is generally five orders of magnitude slower than that in the gas phase 28 , hence, open porosity (mesopore and macropore) is advantageous as it will facilitate molecular diffusion and increase the accessibili ty to the active sites that are located in the microporous channels from the outside 29,30 . As N2 sorption only provides the total porosity -including both open and close porosity -a complementary method is required to discriminate between the open and closed mesopore and macropores.…”
Section: Textural Propertiesmentioning
confidence: 99%
“…The BJH pore size distribution of the TPAOH treated samples shows random mesopores and macropores in the range 10 nm to 160 nm (Figure 2b and Figure S1c), and the pore size increase with the concentration of TPAOH. In liquid phase reactions, the diffusivity of species is generally five orders of magnitude slower than that in the gas phase 28 , hence, open porosity (mesopore and macropore) is advantageous as it will facilitate molecular diffusion and increase the accessibili ty to the active sites that are located in the microporous channels from the outside 29,30 . As N2 sorption only provides the total porosity -including both open and close porosity -a complementary method is required to discriminate between the open and closed mesopore and macropores.…”
Section: Textural Propertiesmentioning
confidence: 99%
“…Similarly, by naively assuming an arrangement of regular dodecahedral cells, the average area of each pentagonal (strut-less) face can be thought to be about 7.8 × 10 4 µm 2 and thus contrasted to the average window area of 3.1 × 10 4 µm 2 reported by the same author for 100 ppi RVC. The values are comparable, but their difference confirms that only a combination of complex 3D structures of different sizes is analogous to the real material; see[58].…”
mentioning
confidence: 52%
“…As Fan et al . reported, open-cell SiC foams clearly are promising materials for continuous-flow chemical applications such as heterogeneous catalysis and distillation [ 2 , 3 ], the X-ray micro-computed tomography characterization results showed that the spatial voxel size of cellular β-SiC foams was 13.6 3 µm 3 , and diffusion coefficient of laminar flow within foams was dramatically increased. Xu et al .…”
Section: Introductionmentioning
confidence: 99%